BS ISO 9809-4. Gas cylinders. Refillable seamless steel gas cylinders. Design, construction and testing. Part 4. Stainless steel cylinders with an Rm value of less than 1 100 MPa (9th September 2020) - British Standards Institution,
No abstract available